Determinants of Indonesia’s Salt Imports in 1990–2024 Period - Ginting, Windy Aurelia Br; Budiningsih, Ni Ketut (CV. Lenggogeni Data Publishing, 2025)
This study aims to analyze the factors influencing salt imports in Indonesia over the period 1990–2024. Despite Indonesia’s substantial marine resource potential, dependence on imported salt remains high, particularly to meet the needs of the food, chemical, and pharmaceutical industries. This condition is primarily driven by the low quality and insufficient quantity of domestic salt production, which has yet to meet industrial purity standards. The study employs annually time-series with secondary data and utilizes Ordinary Least Square (OLS) and the Error Correction Model (ECM) as analytical techniques. The ECM estimation results indicate that all variables under investigation converge toward a long-run equilibrium, demonstrating the presence of cointegration. Both short-run and long-run analyses further reveal that Gross Domestic Product (GDP), domestic salt production, import salt prices, and the exchange rate jointly exert a significant influence on Indonesia’s salt imports. Partially, the long-run and short-run estimations show that GDP and the Rupiah exchange rate have a positive and statistically significant effect on the volume of salt imports. In contrast, import salt prices exhibit a negative and significant effect in the short run, while domestic salt production is found to be statistically insignificant. Based on these findings, it is recommended that policymakers and relevant stakeholders coordinate more closely to align salt import policies with national economic growth dynamics, while simultaneously strengthening domestic salt production capacity through technological modernization and infrastructure development.